MTOR pathway repressing expression of FoxO3 is a potential mechanism involved in neonatal white matter dysplasia. Issue 15 (26th February 2022) - Liu, Xiuyun; Dong, Chen; Liu, Kaiyi; Chen, Huiyao; Liu, Bo; Dong, Xinran; Qian, Yanyan; Wu, Bingbing; Lin, Yifeng; Wang, Huijun; Yang, Lin; Zhou, Wenhao
Abstract: Neonatal white matter dysplasia (NWMD) is characterized by developmental abnormity of CNS white matter, including abnormal myelination. Besides environmental factors such as suffocation at birth, genetic factors are also main causes. Signaling pathway is an important part of gene function and several signaling pathways play important roles in myelination. Here, we performed genetic analysis on a cohort of 138 patients with NWMD and found that 20% (5/25) cause genes which referred to 28.57% (8/28) patients enriched in mammalian target of rapamycin (mTOR) signaling pathway. Depletion of mTOR reduced genesis and proliferation of oligodendrocyte progenitor cells (OPC) during embryonic stage and reduced myelination in corpus callosum besides cerebellum and spinal cord during early postnatal stages which is related to not only differentiation but also proliferation of oligodendrocyte (OL). Transcriptomic analyses indicated that depletion of mTOR in OLs upregulated expression of forkhead box O3 ( FoxO3), which is a repressor of expression of myelin basic protein, and downregulating expression of FoxO3 by short interfering RNA promoted OPCs develop into MBP + OLs. Thus, our findings suggested that mTOR signaling pathway is NWMD-related pathway and mTOR is important for myelination of the entire CNS during early developmental stages through regulating expression of FoxO3 at least partially.